Effects of cetane number improvers on diesel fuel from direct coal liquefaction. Issue 21 (1st November 2016) - Yang, Chao; Liu, Hui; He, Kangkang; Xue, Yuan; Li, Yong; Chang, Xing; Lin, Hualin; Sheng, Han
ABSTRACT: Diesel from direct coal liquefaction possess low sulfur content and good cold flow properties. Nevertheless, its cetane number is only 44, which is much lower than 51 set by EN 590. In this study, the cetane numbers of this diesel and its blends with isooctyl nitrate, tert-butyl peroxybenzoate, acetone, 2-ethoxyethanol, and dibutyl oxalate were measured. Results showed that 0.5% isooctyl nitrate and acetone could increase cetane number from 44 to 53.2 and 52.8, respectively; isooctyl nitrate mixed with 66.7% acetone exhibit positive synergistic effects. The mechanism of these improvers based on the thermal decomposition principle was also explored.